Complete Blood Count Collected Via Venipuncture Versus Peripherally Inserted Central Catheter in Hematological Patients: A Comparison of 2 Methods. Issue 1 (5th January 2022) - Ponticelli, Elena; Clari, Marco; Volpes, Martina; Valenti, Laura; Angioni, Marco; Granero, Daniele; Bert, Mattia; Conti, Alessio; Campagna, Sara
Abstract : Background: The use of peripherally inserted central catheters (PICCs) in cancer care is increasing over traditional central venous catheters. Nurses frequently collect blood by venipuncture when a PICC is inserted, as there is no available evidence to confirm the reliability of blood tests collected through PICCs in adults. Objective: The aim of this study was to assess the reliability of blood samples for complete blood count (CBC) obtained through PICCs as an alternative to venipuncture. Methods: A cross-sectional design was used to recruit adult hematological patients. The blood samples were collected within 5 minutes of each other by a specialist nurse. Hemoglobin, hematocrit, and platelet count were evaluated. To determine method comparison, Passing-Bablok regression, test of linearity, Pearson product-moment correlation coefficient, and Bland-Altman plots were used. Results: Thirty paired blood samples were collected in 29 hematological patients with a mean age of 66.8 years. A statistical difference was found for hemoglobin ( P = .001) and hematocrit ( P = .001) levels, but no clinical difference. The regression models revealed no systematic differences and no proportional differences with a linear relationship between the methods. Bland-Altman plots highlighted a good agreement between methods. Conclusion: Blood samples for CBC drawn by PICCs are as reliable as those collected via venipuncture. Blood sampling via PICC could be recommended in people with hematological malignancies in needs of frequent blood tests. Implications for Practice: Sampling through a PICC provides reliable laboratory results for CBC, and it could reduce patients' discomfort and increase the safety of professionals reducing the risk of accidental percutaneous needlestick injuries.